K.J. Aiyer's judicial dictionary : a complete law lexicon. - Aiyar, Krishna Jagadisa, 1885- (New Delhi : LexisNexis Butterworths, 2007)
Dictionary of terminology mostly used in Indian courtrooms.
SOL
Anupam Gyan Bhandar
Keywords: Law -- India -- Dictionaries